Morphologica evaluation of Pilocarpus microphyllus Stapf Ex Wardleworth (Research, Society and Development, 2021)
This work aimed to evaluate accessions of  jaborandi, and to identify the morphological descriptors for the species. Twenty-five accessions, preserved in vivo at Embrapa Amazônia Oriental, in Belém, PA, were evaluated, totaling 125 individuals, for eight quantitative morphological characters. The data were submitted to multivariate analyzes, direct selection and selection with reanalysis were carried out grouped in two methods and based on the average Euclidean distance used in the formation of the clusters by the UPGMA methods of Tocher's optimization and for the analysis of main components. Of the eight characters evaluated according to the two procedures used, none was shown to be reduntant, so there was no discard. The dissimilarities found based on the Euclidean distance - standardized mean had three shortest distances 0.35; 0.44 and 0.46 between pairs of accessions and allowed to separate them into three divergent groups by the Unweighted Paired Group Method Using ArithmeticAverages and by the Tocher method, there were the formation of four distinct groups. Two characters presented the greatest contributions to the divergence, being width and length of the leaf, with 35.4%. Therefore, the evaluated accessions of jaborandi have morphological variability according to the quantitative characters: number of leaflets / leaf, plant height; leaflet width, petiole length, leaf length, leaf width; length of the leaflet and length of the inflorescence, the characters width and length of the leaf being the ones that most contributed to the divergence between the accessions.